DEVELOPMENT OF LOCOMOTIVE CC 203 MAINTENANCE STRATEGY USING RISK-BASED RELIABILITY CENTERED MAINTENANCE (RCM 3) METHOD - Arfiansyah, Oky; Wiratmaja, I Gusti Nyoman (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
Trains play a vital role in Indonesia's transportation system as they help reduce exhaust emissions and are one of the most environmentally friendly modes of transportation. PT Kereta Api Indonesia (PT KAI) as the largest train operator in Indonesia has an important role in providing reliable and efficient train services. This research analyzes the maintenance strategy applied to locomotive CC 203 and provides recommendations to improve reliability and maintenance cost efficiency using the Risk-Based Reliability Centered Maintenance (RCM 3) method. The RCM analysis results show that by changing the maintenance interval from P24 to P12, P24, and P48 the reliability of the diesel engine system can be improved from 66,3% to 80,2%. In addition, the risk of failure mode occurrence decreases. Although the cost of the proposed maintenance increases, the benefits obtained are much greater including increased system reliability, decreased risk, and potential reduction in corrective maintenance costs. Therefore, this new maintenance recommendation is expected to assist PT KAI in maintaining reliable and efficient operations, as well as anticipating the risks associated with corrective maintenance costs.